2019
DOI: 10.25142/osp.2018.018
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Pharmacological Treatment in Home and Institutional Care of the Elderly

Abstract: Cieľom príspevku je opísať nefarmakologickú liečbu a možnosti jej využitia u seniorov v domácej a ústavnej liečbe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…These interventions mainly include the education of seniors and their families with an emphasis on self-efficacy and daily activities, nursing rehabilitation, prevention of immobility disorders, physical therapy, medical nutrition, dietotherapy, phytotherapy, hydration, mental activation. Common methods include basal stimulation, reminiscence therapy and validation, cognitive rehabilitation, which, however, require completing special courses and certification (Zrubáková et al, 2018). One of the most used dementia treatment modalities is cognitive training, which is based on the training of cognitive functions using quizzes, games, crossword puzzles, work with calendars, newspapers, magazines, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions mainly include the education of seniors and their families with an emphasis on self-efficacy and daily activities, nursing rehabilitation, prevention of immobility disorders, physical therapy, medical nutrition, dietotherapy, phytotherapy, hydration, mental activation. Common methods include basal stimulation, reminiscence therapy and validation, cognitive rehabilitation, which, however, require completing special courses and certification (Zrubáková et al, 2018). One of the most used dementia treatment modalities is cognitive training, which is based on the training of cognitive functions using quizzes, games, crossword puzzles, work with calendars, newspapers, magazines, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the data from a clinical research, Zrubáková et al (2018) found that individual non-pharmacological procedures cannot be performed adequately in after-treatment departments, hospitals and facilities for long-term patients and senior facilities due to an insufficient number of nurses and absence of physiotherapists (as well as other experts). The mutual coordination in the cooperation of medical and social workers, therapeutic pedagogists and psychologists also stagnates.…”
Section: Resultsmentioning
confidence: 99%